Sistem Informasi Laundry Berbasis Web - Maulana, Faris; Kusumah, Fitrah Fajar; Kamilah, Nurul (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to develop a web-based information system using PHP and MySQL for LaundryCare, with the primary goal of recording transactions digitally, providing a module for customers to check their laundry status, and simplifying report generation and transaction monitoring. The Waterfall method was applied, covering requirements analysis, design, development, testing, and system implementation. The results show that the new system successfully reduced the risk of errors and data loss, enhanced transparency with the laundry status module, and expedited and simplified report generation. This system improves operational efficiency and increases customer satisfaction.